Theoretical and empirical comparison of coupling coefficient and refractive index estimation for coupled waveguide fiber - Saktioto, Toto (Rochester Institute of Technology, College of Applied Science and Technology (CAST), 2008)
Power transmission and coupling of coupled waveguide fibers are affected on coupling coefficient. The coupling coefficients obtained in experimental result vary in a wide range. It has a function of separation of fiber axis and refractive index of core and cladding. For empirical formula, coupling coefficient is calculated from experimental result of coupling ratio distribution from 1% until 75%. Theoretically, it has a dependence of some parameters resulting sinusoidal curve. Both empirical and theoretical formulae are compared to obtain new phenomena of refractive index of fibers after fusion.